2016
DOI: 10.1111/psyp.12762
|View full text |Cite
|
Sign up to set email alerts
|

The N400 elicited by homonyms in puns: Two primes are not better than one

Abstract: To comprehend a pun involving a homonym (e.g., The prince with a bad tooth got a crown), both meanings of the homonym must be accessed and selected. Previous ERP studies have shown that the N400 reflects lexicosemantic processing, but none have directly investigated the N400 elicited by homonyms in the unique context of puns. Here, N400 priming effects showed that the dual context of puns (e.g., the primes prince and tooth) did not facilitate homonym processing in comparison to single dominant biasing (e.g., T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
5
1
Order By: Relevance
“…This idea has been frequently used to explain the so-called subordinate-biased effect (Duffy et al, 1988(Duffy et al, , 2001). In the case of a pun, where the two meanings are similarly supported, this model also predicts that the salient (dominant) meaning will be accessed first, then followed by the less salient (subordinate) meaning (Sheridan et al, 2009;Dholakia et al, 2016).…”
Section: Salience Effect In a Less-salient-meaning-biasing Contextmentioning
confidence: 93%
See 1 more Smart Citation
“…This idea has been frequently used to explain the so-called subordinate-biased effect (Duffy et al, 1988(Duffy et al, , 2001). In the case of a pun, where the two meanings are similarly supported, this model also predicts that the salient (dominant) meaning will be accessed first, then followed by the less salient (subordinate) meaning (Sheridan et al, 2009;Dholakia et al, 2016).…”
Section: Salience Effect In a Less-salient-meaning-biasing Contextmentioning
confidence: 93%
“…While in the pun context, no such "reordering" occurred since the balanced pun context could not reverse the frequency advantage of the salient meaning. In another ERP study, Dholakia et al (2016) found that the pun context condition (e.g., The prince with a bad tooth got a crown) elicited smaller N400 amplitudes (i.e., priming effect) on the homonyms than the neutral context condition (e.g., The adult with a bad leg got a crown). However, the pun context did not elicit a larger N400 priming effect in comparison to a single dominant biasing context (e.g., The prince with a bad leg got a crown).…”
Section: Introductionmentioning
confidence: 94%
“…Again, encountering the ambiguous word itself is crucial to this comprehension facilitation, since reading subordinate context alone in a prime sentence (i.e., without the ambiguous word itself being presented) does not facilitate comprehension of the subordinate word-meaning itself when it is read up to a few minutes later (Leinenger & Rayner, 2013). Furthermore, comprehension can be (but is not always; Binder & Morris, 1995) impeded when the meaning of the second encounter is inconsistent with the first, showing that recent experience with a particular word-meaning can also hinder subsequent comprehension in cases where the subsequent encounter has the alternative meaning (Bainbridge, Lewandowsky, & Kirsner, 1993; Copland, 2006; Dholakia, Meade, & Coch, 2016; Simpson & Kang, 1994; Simpson & Kellas, 1989). Together, these very short-term (up to only a few minutes) priming studies clearly demonstrate that word-meaning representations are sensitive to very recent experience with those words, and can update rapidly to accommodate that experience.…”
mentioning
confidence: 99%
“…The literature on semantic priming has shown that targets preceded by related primes tend to elicit smaller N400 amplitudes than those preceded by unrelated primes (for a review, see Kutas & Federmeier, 2011). This "N400 priming" effect has often been used to investigate patterns of meaning activation in homonyms, both in isolation (e.g., Atchley & Kwasny, 2003;Klepousniotou et al, 2012) and biasing context (e.g., Dholakia, Meade, & Coch, 2016;Swaab, Brown, & Hagoort, 2003). The general finding from such studies is that meanings that are highly frequent or supported by surrounding context are more readily available, and therefore produce greater N400 priming.…”
Section: Methodsmentioning
confidence: 99%